A mixed control system for active suspension for off-road vehicles - Sabaneh, Omar A. O.; Faris, Waleed Fekry; Okasha, Mohamed Elsayed Aly Abd Elaziz; Hasbullah, Faried (Inderscience Enterprises Ltd., 2016)
Since the passive suspension system is not enough for creating good compromise between road handling and ride comfort for off-road vehicles, this paper presents a study on the application of an active suspension system. In this work, a neuro-fuzzy controller (NFC) is developed for two and three-axle half-car off-road vehicle models. A fuzzy logic controller (FLC) is employed as a benchmark for the NFC. The system designed for this study takes in two types of road disturbances as inputs, namely pothole and random road inputs. The sprung mass vertical and pitch accelerations are the criteria employed for the evaluation of the ride comfort, while the tyre deflection is used for the road handling. The results demonstrate that the NFC has a superior performance over the FLC in creating excellent ride comfort and good road handling without compromising the rattle-space requirement. On the other hand, the NFC requires higher actuation forces than the FLC as it gives a better performance that requires more control effort.